High-performance sodium ion battery hard carbon negative electrode material and preparation method thereof

By using biomass materials and metal chloride salt catalysts, combined with catalytic carbonization and microwave-assisted heat treatment, hard carbon materials with rich microporous structures and short-range dense layer structures were prepared, which solved the low specific capacity and magnification of the negative electrode material of sodium ion battery. The poor performance problem achieves the performance of sodium ion batteries with high energy density and long life.

CN119133446APending Publication Date: 2024-12-13TIANXING CENTURY NEW MATERIAL TECH (HANGZHOU) CO LTD
View PDF 0 Cites 2 Cited by

Patent Information

Application Number
CN202311408398.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-10-27
Publication Date
2024-12-13

AI Technical Summary

Technical Problem

The existing hard carbon anode materials of sodium ion batteries have problems such as low specific capacity, low first-circuit Coulomb efficiency, poor rate performance, and poor cycle stability, which limits the development of high-energy, high-power density sodium ion batteries.

Method used

Using biomass materials as carbon source and metal chloride as catalyst, a two-step carbonization method combining catalytic carbonization with microwave-assisted heat treatment and chemical vapor deposition treatment was carried out to prepare a rich micropore structure and short-range dense layer. Structured low exterior specific surface area hard carbon material.

Benefits of technology

Achieve high specific capacity (>350mAh/g), high first-round Coulomb efficiency (>90%), high rate performance (capacity retention rate greater than 75% at 4C high rate) and excellent cycle performance, improving the energy of the battery cell Density, power density and cycle life.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119133446A_ABST
    Figure CN119133446A_ABST
Patent Text Reader

Abstract

The invention discloses a high-performance sodium-ion battery hard carbon negative electrode material and a preparation method thereof, and the preparation method comprises the following steps: uniformly mixing a carbon source precursor with metal chlorate, carrying out a catalytic carbonization reaction at 400-600 DEG C, and after the reaction, carrying out acid pickling and water washing to obtain a solid A; carrying out acid pickling and water washing on the solid A until the solid A is neutral, and carrying out microwave-assisted heat treatment at 1100-1500 DEG C to obtain a solid C; and crushing the solid C and carrying out chemical vapor deposition treatment to finally obtain the high-performance sodium-ion battery hard carbon negative electrode material. The hard carbon material prepared by the method has the advantages of abundant micropore structures, short-distance tight arrangement of layer structures, proper carbon layer spacing and low external specific surface area, and is suitable for a hard carbon negative electrode material of a high-energy and high-power-density sodium ion battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of sodium ion batteries, and in particular to a sodium ion battery hard carbon negative material and a preparation method thereof. Background Art

[0002] In recent years, with the rising price of lithium salts and the increasingly serious problem of uneven distribution of lithium resources, the development of a new generation of energy storage technology to replace lithium-ion batteries has become a consensus in the energy storage field. Sodium-ion batteries have become a new generation of energy storage stars due to their advantages such as abundant sodium resources, high safety, low temperature and fast charging performance.

[0003] However, the main bottleneck hindering the commercialization of sodium-ion batteries is the negative electrode material. Compared with other materials, hard carbon materials are considered to be the most promising negative electrode materials for sodium-ion batteries due to their low potential platform and high reversibility. However, they have the disadvantages of low specific capacity, low first-cycle coulombic efficiency, poor rate performance, and poor cycle stability, which seriously limit the development of sodium-ion batteries with high energy and high power density. The sodium storage capacity of hard carbon is mainly contributed by three sodium storage methods: defect adsorption, interlayer intercalation, and closed-pore filling. Increasing the microporous structure and layer structure inside the hard carbon, constructing a suitable carbon layer spacing, and reducing the external specific surface area of ​​the material are important ways to improve low capacity, low first-cycle coulombic efficiency, and improve rate performance and cycle stability. Summary of the invention

[0004] The technical problem solved by the present invention is: in order to develop a hard carbon material with rich microporous structure and rich short-range densely packed layer structure, as well as low specific surface area, so as to realize high specific capacity, high first-cycle coulombic efficiency, high rate and long life when applied to the negative electrode of sodium ion battery, the present invention provides a method for preparing a high-performance hard carbon negative electrode material for sodium ion battery. The method uses biomass material as a carbon source and metal chloride as a carbonization catalyst, and uses a two-step carbonization method combining catalytic carbonization and microwave-assisted heat treatment, as well as chemical vapor deposition post-treatment, to finally obtain a hard carbon negative electrode material with rich microporous structure, short-range densely packed layer structure, appropriate carbon layer spacing, low external specific surface area, and suitable for high energy and high power density sodium ion batteries.

[0005] The technical solution adopted to achieve the purpose of the present invention is:

[0006] In the first aspect, an embodiment of the present invention provides a high-performance hard carbon negative electrode material for a sodium ion battery, characterized in that the macroscopic morphology of the hard carbon negative electrode material is powdery, and the microscopic morphology is irregular block particles, and the particle size D50 of the irregular block particles is 5-10 μm; the hard carbon negative electrode material has both a rich microporous structure and a rich short-range close-packed layer structure, a pore diameter of less than 2 nm, a carbon layer spacing d002 of 0.37-0.39 nm, a crystallite size basal width La of 2-3 nm, a longitudinal length Lc greater than 1.5 nm, and a Raman D peak intensity to G peak intensity ratio I D / I G In 2-3; the specific surface area of ​​the hard carbon material measured by nitrogen adsorption and desorption is less than 5m 2 / g.

[0007] In a second aspect, an embodiment of the present invention provides a method for preparing a high-performance sodium ion battery hard carbon negative electrode material according to the first aspect, comprising the following steps:

[0008] S1: mechanically mixing the carbon source precursor and the metal chloride solid to obtain a mixture A;

[0009] S2: Under an inert atmosphere and at 400-600° C., the mixed material A is subjected to catalytic carbonization treatment to obtain a solid B;

[0010] S3: acid-washing and water-washing the solid B, and then drying to obtain a solid C;

[0011] S4: in an inert atmosphere, further subjecting solid C to microwave-assisted heat treatment at a temperature of 1100-1500° C. to obtain solid D;

[0012] S5: crushing the solid D to obtain powder E;

[0013] S6: Under the condition of 600-900° C., an organic gas is introduced to perform chemical vapor deposition treatment on the above powder E to obtain the high-performance sodium ion battery hard carbon negative electrode material as described in claim 1.

[0014] Preferably, the carbon source precursor is a biomass raw material, selected from at least one of sawdust, fruit shells, bamboo chips, coconut shells, walnut shells, lignin and cellulose.

[0015] Preferably, the metal chloride is acidic and is selected from at least one of zinc chloride, cupric chloride, ferrous chloride and magnesium chloride.

[0016] Preferably, in S1, the carbon source precursor and the metal chloride are mixed in a mass ratio of 1:1-1:3.

[0017] Preferably, in S2, the temperature is raised to 400-600°C at a heating rate of 5-10°C / min, and the mixed material A is subjected to catalytic carbonization treatment for 60-240 min.

[0018] Preferably, in S3, the solid B is acid-washed and water-washed for multiple times until the filtrate is neutral.

[0019] Preferably, in S4, the temperature is raised to 1100-1500° C. at a heating rate of 50-100° C. / min, and the solid C is subjected to high-temperature carbonization treatment for 10-40 min.

[0020] Preferably, in S4, the microwave frequency is 2.4-2.6 GHz, and the microwave power is 0.5-1.4 kW.

[0021] Preferably, in S6, the organic gas is selected from at least one of benzene, toluene, xylene, propane, butane, acetylene and methane.

[0022] Preferably, in S6, the flow rate of the organic gas is 1-100 L / min, and the reaction time of chemical vapor deposition is 60-180 min.

[0023] Preferably, the inert atmosphere is selected from at least one of a nitrogen atmosphere, an argon atmosphere and a helium atmosphere.

[0024] Compared with the prior art, the present invention has the following beneficial effects:

[0025] 1. The preparation method of the high-performance sodium ion battery hard carbon negative electrode material provided by the present invention uses metal chloride as a catalyst for carbonization. The metal chloride can catalyze dehydration during the carbonization process, reduce the release of organic volatiles, and greatly improve the carbon yield. In addition, the metal chloride can also provide a skeleton during the carbonization process. After carbonization, the skeleton is removed by acid washing and water washing, and the surface of the carbon is exposed to form a rich pore structure, which is conducive to providing rich sodium storage sites, so that the hard carbon material has a high specific capacity (at a rate of 0.1C, the specific capacity is greater than 350mAh / g).

[0026] 2. The preparation method of the high-performance sodium ion battery hard carbon negative electrode material provided by the present invention, through microwave-assisted heat treatment, makes the material have a rich short-range tight layer structure, and the appropriate carbon layer spacing is 0.37-0.39nm, which is conducive to providing a fast transmission channel for solid-phase diffusion of sodium ions. Compared with traditional high-temperature heating, microwave-assisted heat treatment has the characteristics of fast heating rate and short reaction time. Rapid high-temperature heat treatment can make the carbon microcrystalline layer structure rearrangement rate faster than the epitaxial growth rate, so that a short-range tight layer structure can be formed, and the layer spacing can be reasonably controlled at 0.37-0.39nm. Appropriate interlayer spacing plays a key role in the solid-phase diffusion of sodium ions. When the interlayer spacing is less than 0.37nm, the diffusion of sodium ions between layers is severely hindered and can only diffuse through limited pores. When the interlayer spacing is between 0.37-0.39nm, sodium ions can achieve a jumping transmission mechanism along the carbon wall, which has the characteristics of fast transmission rate. When the interlayer spacing is greater than 0.39nm, the diffusion of sodium ions between layers can only follow the concentration gradient diffusion mechanism of Fick's second law, which is the same as the mechanism of diffusion in pores, and the diffusion rate is slow. Therefore, microwave-assisted heat treatment is used to achieve a rich short-range tightly packed layer structure and a suitable carbon interlayer spacing of 0.37-0.39nm, which is conducive to improving the solid-phase diffusion rate of sodium ions and making the hard carbon material have high-rate characteristics (at 4C high rate, the capacity retention rate is greater than 75%).

[0027] 3. The preparation method of the high-performance sodium ion battery hard carbon negative electrode material provided by the present invention can further reduce the external specific surface area of ​​the material through chemical vapor deposition coating, thereby reducing the side reactions of the electrolyte on the surface of the carbon material, so that the hard carbon material has an ultra-high first coulombic efficiency (>90%).

[0028] 4. The high-performance sodium ion battery hard carbon negative electrode material provided by the present invention exhibits excellent electrochemical properties, including high specific capacity (>350mAh / g), high first-cycle coulombic efficiency (>90%), high rate performance (capacity retention rate is greater than 75% at 4C high rate), and excellent cycle performance. Applying it to sodium ion batteries is expected to greatly improve the energy density, power density and cycle life of the battery cell.

[0029] 5. The present invention uses biomass materials as precursors, which have a wide source and low cost. In addition, the preparation process is simple, so it has a good cost advantage. BRIEF DESCRIPTION OF THE DRAWINGS

[0030] Figure 1 This is a SEM image of the high-performance hard carbon negative electrode material for sodium ion batteries in Example 1 of the present invention.

[0031] Figure 2 This is a TEM image of the high-performance hard carbon negative electrode material for sodium ion batteries in Example 1 of the present invention.

[0032] Figure 3 This is the XRD diagram of the high-performance hard carbon negative electrode material for sodium ion batteries in Example 1 of the present invention.

[0033] Figure 4 This is the charge and discharge curve when the hard carbon material in Example 1 of the present invention is used as the negative electrode of a sodium ion battery.

[0034] Figure 5 This is a rate performance diagram of the hard carbon material in Example 1 of the present invention when used as the negative electrode of a sodium ion battery.

[0035] Figure 6 This is a cycle performance diagram of the hard carbon material in Example 1 of the present invention when used as the negative electrode of a sodium ion battery.

[0036] Figure 7 This is a TEM image of the high-performance sodium ion battery hard carbon negative electrode material in Comparative Example 1 of the present invention.

[0037] Figure 8 This is the XRD diagram of the high-performance hard carbon negative electrode material for sodium ion batteries in Comparative Example 1 of the present invention.

[0038] Fig. 9 This is the charge and discharge curve when the hard carbon material in Comparative Example 1 of the present invention is used as the negative electrode of a sodium ion battery.

[0039] Fig.10 This is a rate performance diagram when the hard carbon material in Comparative Example 1 of the present invention is used as the negative electrode of a sodium ion battery.

[0040] Fig.11 This is a TEM image of the high-performance sodium ion battery hard carbon negative electrode material in Comparative Example 2 of the present invention.

[0041] Fig.12 This is the XRD diagram of the high-performance hard carbon negative electrode material for sodium ion batteries in Comparative Example 2 of the present invention.

[0042] Fig.13 This is the charge and discharge curve when the hard carbon material in Comparative Example 2 of the present invention is used as the negative electrode of a sodium ion battery.

[0043] Fig.14 This is a rate performance diagram when the hard carbon material in Comparative Example 2 of the present invention is used as the negative electrode of a sodium ion battery. DETAILED DESCRIPTION

[0044] The present invention is now further described in detail. The embodiments described below are exemplary and intended to be used to explain the present invention, but cannot be understood as limiting the present invention. All other embodiments obtained by ordinary technicians in this field without creative work based on the embodiments of the present invention belong to the scope of protection of the present invention.

[0045] The embodiment of the present invention provides a method for preparing a high-performance hard carbon negative electrode material for a sodium ion battery, comprising the following steps:

[0046] S1: mechanically mixing the carbon source precursor and the metal chloride solid to obtain a mixture A;

[0047] S2: Under an inert atmosphere and at 400-600° C., the mixed material A is subjected to catalytic carbonization treatment to obtain a solid B;

[0048] S3: acid-washing and water-washing the solid B, and then drying to obtain a solid C;

[0049] S4: In an inert atmosphere, further subjecting solid C to microwave-assisted heat treatment at a temperature of 1100-1500° C. to obtain solid D;

[0050] S5: crushing the solid D to obtain powder E;

[0051] S6: Under the condition of 600-900° C., an organic gas is introduced to perform chemical vapor deposition treatment on the above powder E to obtain the high-performance sodium ion battery hard carbon negative electrode material as described in claim 1.

[0052] Specifically, the present invention uses biomass materials as carbon source precursors, mixes metal chlorides as catalysts with biomass materials, and then heats to 400-600°C at a heating rate of 5-10°C / min in an inert atmosphere, and catalytic carbonization treatment is performed on the mixture for 60-240min. During the carbonization process, cellulose, hemicellulose, and lignin contained in the biomass material will depolymerize, releasing a large amount of small-molecule organic volatiles. Under the catalytic dehydration of metal chlorides, the small-molecule organic volatiles will be dehydrated and polymerized again to form oligomers and coke, thereby reducing the release of organic volatiles and greatly improving the carbon yield. The large amount of water and carbon dioxide molecular gas generated during the carbonization process is conducive to pore formation in the material. In addition, the metal chloride is liquid during the high-temperature carbonization process, has good fluidity, can fully infiltrate the pores of the solid material, and can also play a catalytic role inside the material. In addition, the metal chloride can also act as a skeleton, allowing the new carbon structure to grow along the metal chloride. Furthermore, after carbonization, the metal chloride is removed by acid washing and water washing, and the internal surface of the carbon is exposed again, forming a large number of pore structures.

[0053] Specifically, the present invention provides a method for preparing a high-performance sodium ion battery hard carbon negative electrode material, in which S4 is further subjected to microwave-assisted heat treatment for 10-40 min at a heating rate of 50-100°C / min to 1100-1500°C under an inert atmosphere, with a microwave frequency of 2.4-2.6 GHz and a microwave power of 0.5-1.4 kW on the solid obtained in the above S3. During conventional heat treatment, the layer structure of graphite microcrystals will be rearranged, and the microcrystals will grow epitaxially, increasing the size of the microcrystals. Since microwave-assisted heat treatment has the characteristics of fast heating rate and short reaction time compared to conventional heat treatment, rapid high-temperature heat treatment can make the rearrangement rate of the layer structure significantly faster than the epitaxial growth rate, so that the hard carbon material can form a short-range tightly packed layer structure and retain most of the microporous structure. In addition, the carbon layer spacing can be optimized.

[0054] Specifically, in the method for preparing a high-performance sodium ion battery hard carbon negative electrode material provided by the present invention, in S5, the solid obtained in S4 is crushed to obtain a powder material, and the D50 of the powder material is 5-10 μm.

[0055] Specifically, the method for preparing a high-performance sodium ion battery hard carbon negative electrode material provided by the present invention, in said S6, at 600-900°C, an organic gas is introduced at a flow rate of 1-100L / min, and the powder obtained in said S5 is subjected to chemical vapor deposition for 60-180min to obtain a high-performance sodium ion battery hard carbon negative electrode material. A dense and stable soft carbon coating layer is formed on the hard carbon surface by chemical vapor deposition, so that the external specific surface area of ​​the hard carbon material is further reduced, and at the same time, the conductivity of the material is improved.

[0056] Specifically, the biomass raw material selected in the present invention is rich in cellulose, lignin, and hemicellulose, and is selected from at least one of sawdust, fruit shells, bamboo chips, coconut shells, walnut shells, lignin, and cellulose.

[0057] Specifically, the metal chloride selected in the present invention is acidic and is selected from at least one of zinc chloride, cupric chloride, ferrous chloride and magnesium chloride.

[0058] In order to make the above-mentioned objects, features and advantages of the present invention more obvious and easy to understand, specific embodiments of the present invention are described in detail below with reference to the accompanying drawings.

[0059] Example 1

[0060] This embodiment provides a high-performance hard carbon negative electrode material for sodium ion batteries. The particle size D50 of the carbon negative electrode material is 6.8 μm and the specific surface area is 3.8 m 2 / g, with rich pore structure, pore diameter less than 2nm, crystallite size basal width La is 2.7nm, longitudinal length Lc is 1.8nm, carbon layer distance d002 is 0.375nm, Raman D peak intensity and G peak intensity ratio is I D / I G is 2.3.

[0061] The preparation method of the carbon negative electrode material comprises the following steps:

[0062] Step 1, using 50 kg of sawdust as a precursor, crushing it into a particle size of 40-60 mesh, and physically and mechanically mixing it with zinc chloride solid at a mass ratio of 1:2 to obtain a mixture A;

[0063] Step 2, in a nitrogen atmosphere, the temperature is raised to 500° C. at a heating rate of 5° C. / min, and the mixed material A is carbonized in a heating furnace for 180 min to obtain a solid B;

[0064] Step 3, washing solid B in 100 L of 5 wt% hydrochloric acid for 24 h, then washing with water until the filtrate is neutral, and drying to obtain solid C.

[0065] Step 4, under a nitrogen atmosphere, raise the temperature to 1300° C. at a heating rate of 80° C. / min, and subject solid C to microwave heat treatment in an industrial microwave oven for 30 min to obtain solid D, with a microwave frequency of 2.45 GWh and a microwave power of 1.4 kW.

[0066] Step 5, crushing the solid D to obtain powder E, the D50 of the powder material is 5.6 μm.

[0067] Step 6, at 750° C., benzene vapor is introduced at a flow rate of 50 L / min, and powder E is chemically vapor deposited in a rotary kiln for 120 min to obtain the above-mentioned high-performance sodium ion battery hard carbon negative electrode material.

[0068] The SEM of the high performance hard carbon negative electrode material for sodium ion battery provided in Example 1 is as follows Figure 1 As shown, it can be seen that the prepared high-performance sodium ion battery hard carbon negative electrode material shows a typical block morphology.

[0069] TEM of the high performance sodium ion battery hard carbon negative electrode material provided in Example 1 is as follows Figure 2 As shown, it can be seen that there are abundant pore structures and abundant short-range tight layer structures inside the hard carbon material, and the average pore diameter is less than 2nm.

[0070] The XRD spectrum of the high performance sodium ion battery hard carbon negative electrode material provided in Example 1 is as follows Figure 3As shown, the root spectrum calculated that the basal width La of the crystallite size is 2.7nm, the longitudinal length Lc is 1.8nm, and the carbon sheet interlayer spacing d002 is 0.375nm.

[0071] The electrochemical properties of the hard carbon negative electrode material prepared in this embodiment were tested. The hard carbon negative electrode material was used as the negative electrode active material, and polyvinylidene fluoride (PVDF) was used as a binder. It was mixed evenly with conductive carbon black in a mass ratio of 90:5:5 in NMP (N-methylpyrrolidone) solvent, coated into an electrode film, placed in a vacuum drying oven at 120°C for 12 hours, and rolled and punched to obtain a hard carbon negative electrode sheet; a metal sodium sheet was used as a counter electrode, 1 mol / L NaPF6 (EC:DEC=1:1) was used as an electrolyte, and the hard carbon negative electrode sheets obtained above were assembled into 2032 button batteries in a glove box to test their electrochemical properties. See Figure 4 , Figure 5 , Figure 6 As shown, at a 0.1C rate, the specific capacity reaches 395mAh / g and the first efficiency reaches 91%; at a 4C rate, the specific capacity reaches 300mAh / g and the capacity retention rate is 76%; at a 2C rate (1A / g), after 1000 cycles, the capacity retention rate is 80%.

[0072] Example 2

[0073] This embodiment provides a high-performance hard carbon negative electrode material for sodium ion batteries. The particle size D50 of the carbon negative electrode material is 7.2 μm and the specific surface area is 3.6 m 2 / g, with rich pore structure, pore diameter less than 2nm, crystallite size basal width La is 2.5nm, longitudinal length Lc is 2.0nm, carbon layer distance d002 is 0.383nm, Raman D peak intensity and G peak intensity ratio I D / I G is 2.4.

[0074] The preparation method of the carbon negative electrode material comprises the following steps:

[0075] Step 1, using 50 kg of coconut shell as a precursor, crushing it into a particle size of 40-60 mesh, and physically and mechanically mixing it with copper chloride solid in a mass ratio of 1:1 to obtain a mixture A;

[0076] Step 2, in a nitrogen atmosphere, the temperature is raised to 600° C. at a heating rate of 5° C. / min, and the mixed material A is carbonized in a heating furnace for 180 min to obtain a solid B;

[0077] Step 3, washing solid B in 100 L of 5 wt% hydrochloric acid for 24 h, then washing with water until the filtrate is neutral, and drying to obtain solid C.

[0078] Step 4, under a nitrogen atmosphere, increase the temperature to 1300° C. at a heating rate of 50° C. / min, and subject solid C to microwave heat treatment in an industrial microwave oven for 20 min to obtain solid D, with a microwave frequency of 2.45 GWh and a microwave power of 1.3 kW.

[0079] Step 5, crushing the solid D to obtain powder E, the D50 of the powder material is 6.8 μm.

[0080] Step 6, at 750° C., benzene vapor is introduced at a flow rate of 50 L / min, and powder E is chemically vapor deposited in a rotary kiln for 90 minutes to obtain the above-mentioned high-performance sodium ion battery hard carbon negative electrode material.

[0081] The detection and testing process of the hard carbon negative electrode material for the sodium ion battery refers to the relevant content of Example 1; the hard carbon negative electrode has a specific capacity of 360mAh / g and an initial efficiency of 90% at a rate of 0.1C; at a rate of 4C, the specific capacity reaches 270mAh / g and the capacity retention rate is 75%; at a rate of 2C (1A / g), after 1000 cycles, the capacity retention rate is 82%.

[0082] Example 3

[0083] This embodiment provides a high-performance hard carbon negative electrode material for sodium ion batteries. The particle size D50 of the carbon negative electrode material is 6.4 μm and the specific surface area is 4.2 m 2 / g, with rich pore structure, pore diameter less than 2nm, crystallite size basal width La is 2.8nm, longitudinal length Lc is 1.6nm, carbon layer distance d002 is 0.385nm, Raman D peak intensity and G peak intensity ratio is I D / I G is 2.7.

[0084] The preparation method of the carbon negative electrode material comprises the following steps:

[0085] Step 1, using 50 kg of bamboo chips as a precursor, crushing it into a particle size of 40-60 mesh, and physically and mechanically mixing it with magnesium chloride solid at a mass ratio of 1:2 to obtain a mixture A;

[0086] Step 2, in a nitrogen atmosphere, the temperature is raised to 550° C. at a heating rate of 5° C. / min, and the mixed material A is carbonized in a heating furnace for 240 min to obtain a solid B;

[0087] Step 3, washing solid B in 120 L of 5 wt% hydrochloric acid for 24 h, then washing with water until the filtrate is neutral, and drying to obtain solid C.

[0088] Step 4, under a nitrogen atmosphere, raise the temperature to 1400° C. at a heating rate of 100° C. / min, and subject solid C to microwave heat treatment in an industrial microwave oven for 30 min to obtain solid D, with a microwave frequency of 2.45 GWh and a microwave power of 1.4 kW.

[0089] Step 5, crushing the solid D to obtain powder E, the D50 of the powder material is 5.5 μm.

[0090] Step 6, at 600° C., propane is introduced at a flow rate of 30 L / min, and powder E is chemically vapor deposited in a rotary furnace for 120 min to obtain the above-mentioned high-performance sodium ion battery hard carbon negative electrode material.

[0091] The detection and testing process of the hard carbon negative electrode material for the sodium ion battery refers to the relevant content of Example 1; the hard carbon negative electrode has a specific capacity of 380 mAh / g and an initial efficiency of 91% at a 0.1C rate; at a 4C rate, the specific capacity reaches 285 mAh / g and the capacity retention rate is 75%; at a 2C rate (1 A / g), after 1000 cycles, the capacity retention rate is 80%.

[0092] Example 4

[0093] This embodiment provides a high-performance hard carbon negative electrode material for sodium ion batteries. The particle size D50 of the carbon negative electrode material is 5.2 μm and the specific surface area is 3.9 m 2 / g, with rich pore structure, pore diameter less than 2nm, crystallite size basal width La is 3.0nm, longitudinal length Lc is 1.6nm, carbon layer distance d002 is 0.370nm, Raman D peak intensity and G peak intensity ratio is I D / I G is 2.2.

[0094] The preparation method of the carbon negative electrode material comprises the following steps:

[0095] Step 1, using 50 kg of walnut shells as a precursor, crushing them into a particle size of 40-60 mesh, and physically and mechanically mixing them with zinc chloride solid at a mass ratio of 1:1.5 to obtain a mixture A;

[0096] Step 2, in a nitrogen atmosphere, the temperature is raised to 530° C. at a heating rate of 5° C. / min, and the mixed material A is carbonized in a heating furnace for 120 min to obtain a solid B;

[0097] Step 3, washing solid B in 100 L of 5 wt% hydrochloric acid for 24 h, then washing with water until the filtrate is neutral, and drying to obtain solid C.

[0098] Step 4: In a nitrogen atmosphere, the temperature is raised to 1300°C at a heating rate of 100°C / min, and the solid C is subjected to microwave heat treatment in an industrial microwave oven for 40 minutes to obtain a solid D. The microwave frequency is 2.45 GWh and the microwave power is 1.4 kW.

[0099] Step 5, crushing the solid D to obtain powder E, the D50 of the powder material is 5 μm.

[0100] Step 6, at 900° C., methane is introduced at a flow rate of 70 L / min, and powder E is chemically vapor deposited in a rotary furnace for 120 min to obtain the above-mentioned high-performance sodium ion battery hard carbon negative electrode material.

[0101] The detection and testing process of the hard carbon negative electrode material for the sodium ion battery refers to the relevant content of Example 1; the hard carbon negative electrode has a specific capacity of 375 mAh / g and an initial efficiency of 92% at a 0.1C rate; at a 4C rate, the specific capacity reaches 289 mAh / g and the capacity retention rate is 77%; at a 2C rate (1 A / g), after 1000 cycles, the capacity retention rate is 85%.

[0102] Comparative Example 1

[0103] This comparative example provides a high-performance hard carbon negative electrode material for sodium ion batteries. The particle size D50 of the carbon negative electrode material is 6.0 μm, and the specific surface area is 4.0 m 2 / g, the pore structure is not rich, the basal width La of the crystallite size is 4.0nm, the longitudinal length Lc is 2.2nm, the carbon layer distance d002 is 0.358nm, and the Raman D peak intensity and G peak intensity ratio are I D / I G is 1.4.

[0104] The preparation method of the carbon negative electrode material comprises the following steps:

[0105] Step 1, using 50 kg of sawdust as a precursor, crushing it into a particle size of 40-60 mesh, heating it to 500° C. at a heating rate of 10° C. / min in a nitrogen atmosphere, and pre-carbonizing the sawdust in a heating furnace for 120 min to obtain solid A;

[0106] Step 2: In a nitrogen atmosphere, the temperature is raised to 1300° C. at a heating rate of 5° C. / min, and solid A is subjected to a conventional high-temperature carbonization treatment in a high-temperature carbonization furnace for 120 min to obtain powder B.

[0107] Step 3, at 750° C., benzene vapor is introduced at a flow rate of 50 L / min, and powder D is chemically vapor deposited in a rotary kiln for 120 min to obtain the above-mentioned high-performance sodium ion battery hard carbon negative electrode material.

[0108] TEM of the high performance hard carbon negative electrode material for sodium ion battery provided in Comparative Example 1 is as follows Figure 7 As shown, it can be seen that the internal pore structure of the prepared sodium ion hard carbon material is underdeveloped, and the graphite crystallite size is large and the interlayer spacing is small.

[0109] The XRD spectrum of the high performance sodium ion battery hard carbon negative electrode material provided in Comparative Example 1 is as follows Figure 8 As shown, the root spectrum calculated that the basal width La of the crystallite size is 4.0nm, the longitudinal length Lc is 2.2nm, and the carbon sheet interlayer spacing d002 is 0.358nm.

[0110] The detection and testing process of the hard carbon negative electrode material for the sodium ion battery is shown in the relevant content of Example 1; Fig. 9 , Fig.10 At a rate of 0.1C, the specific capacity of the hard carbon negative electrode reached 285mAh / g, and the first efficiency reached 88%; at a rate of 4C, the specific capacity reached 85.5mAh / g, and the capacity retention rate was 30%; at a rate of 2C (1A / g), after 1000 cycles, the capacity retention rate was 74%.

[0111] Comparative Example 2

[0112] This comparative example provides a high-performance hard carbon negative electrode material for sodium ion batteries. The particle size D50 of the carbon negative electrode material is 6.0 μm, and the specific surface area is 4.0 m 2 / g, the pore structure is rich, but the layer structure is disordered, the interlayer spacing is wide, the base width La of the crystallite size is 1.7nm, the longitudinal length Lc is 1.4nm, the carbon interlayer distance d002 is 0.402nm, and the Raman D peak intensity and G peak intensity ratio are I D / I G is 3.2.

[0113] The preparation method of the carbon negative electrode material comprises the following steps:

[0114] Step 1, using 50 kg of sawdust as a precursor, crushing it into a particle size of 40-60 mesh, and physically and mechanically mixing it with zinc chloride solid at a mass ratio of 1:2 to obtain a mixture A;

[0115] Step 2, in a nitrogen atmosphere, the temperature is raised to 500° C. at a heating rate of 5° C. / min, and the mixed material A is carbonized in a heating furnace for 180 min to obtain a solid B;

[0116] Step 3, washing solid B in 100 L of 5 wt% hydrochloric acid for 24 h, then washing with water until the filtrate is neutral, and drying to obtain solid C.

[0117] Step 4, crushing the solid C to obtain powder D, the D50 of the powder material is 5.6 μm.

[0118] Step 6, at 750° C., benzene vapor is introduced at a flow rate of 50 L / min, and powder D is chemically vapor deposited in a rotary furnace for 600 min to obtain the above-mentioned high-performance sodium ion battery hard carbon negative electrode material.

[0119] TEM images of the high performance hard carbon negative electrode material for sodium ion batteries provided in Comparative Example 2 are as follows Fig.11 As shown, it can be seen that the internal pore structure of the prepared sodium ion hard carbon material is well developed, but the layer structure of the graphite microcrystals is disordered and the interlayer spacing is large.

[0120] The XRD spectrum of the high performance sodium ion battery hard carbon negative electrode material provided in Comparative Example 2 is as follows Fig.12 As shown, the root spectrum calculated that the basal width La of the crystallite size is 1.7nm, the longitudinal length Lc is 1.4nm, and the carbon sheet interlayer spacing d002 is 0.402nm.

[0121] The detection and testing process of the hard carbon negative electrode material for the sodium ion battery is shown in the relevant content of Example 1; Fig.13 , Fig.14 At a rate of 0.1C, the specific capacity of the hard carbon negative electrode reaches 350mAh / g, and the first efficiency reaches 85%; at a rate of 4C, the specific capacity reaches 70mAh / g, and the capacity retention rate is 20%; at a rate of 2C (1A / g), after 1000 cycles, the capacity retention rate is 74%.

[0122] Comparative Example 3

[0123] This comparative example provides a high-performance hard carbon negative electrode material for sodium ion batteries. The particle size D50 of the carbon negative electrode material is 7.3 μm, and the specific surface area is 21.8 m 2 / g, with rich pore structure, the pore diameter is less than 2nm, the basal width La of the crystallite size is 2.5nm, the longitudinal length Lc is 1.8nm, the carbon layer distance d002 is 0.380nm, and the Raman D peak intensity and G peak intensity ratio are I D / I G is 2.6.

[0124] The preparation method of the carbon negative electrode material comprises the following steps:

[0125] Step 1, using 50 kg of sawdust as a precursor, crushing it into a particle size of 40-60 mesh, and physically and mechanically mixing it with zinc chloride solid at a mass ratio of 1:2 to obtain a mixture A;

[0126] Step 2, in a nitrogen atmosphere, the temperature is raised to 500° C. at a heating rate of 5° C. / min, and the mixed material A is carbonized in a heating furnace for 180 min to obtain a solid B;

[0127] Step 3, washing solid B in 100 L of 5 wt % hydrochloric acid for 24 h, then washing with water until the filtrate is neutral, and drying to obtain powder C.

[0128] Step 4, under a nitrogen atmosphere, increase the temperature to 1300°C at a heating rate of 80°C / min, and perform microwave heat treatment on solid C in an industrial microwave oven for 30 minutes to obtain the carbon material of Comparative Example 3 above, with a microwave frequency of 2.45 GWh and a microwave power of 1.4 kW.

[0129] The detection and testing process of the hard carbon negative electrode material for the sodium ion battery refers to the relevant content of Example 1; the specific capacity of the hard carbon negative electrode reaches 307mAh / g, the first efficiency reaches 73%, and at a rate of 4C, the specific capacity reaches 184.2mAh / g, the capacity retention rate is 60%, and after 1000 cycles, the capacity retention rate is 65%.

[0130] Among them, in each embodiment and comparative example of the present invention, the "particle size D50" measurement method is: according to the national standard "GB / T19077.1-2003 Laser Particle Size Analysis-Laser Diffraction Method", a laser particle size analyzer is used for testing, and the sample to be tested that has been dispersed by an ultrasonic disperser is placed in a low-power wet centrifugal pump circulation system. When the particles pass through the sample chamber, the laser light source emitted from the semiconductor element is irradiated onto the particle group passing through the perspective slot, which appears as scattered light. The diffracted light is sensed by the sensor, and then the detector composed of a semicircular, high-angle front, and rear silicon photodiodes collects signals and centrally processes them with the CPU, which is displayed as particle size distribution data.

[0131] The measurement method of "basal width La, longitudinal length Lc, and interlayer spacing d002 of crystallite size" is as follows: the crystal structure of the prepared material is analyzed using the Ultima IV-185 X-ray diffractometer of Japan Rigaku Company, wherein the test parameters are: Cu / Kα ray, λ=1.5406A, voltage 40kV, current 40mA, scanning speed 8° / min, step length 0.02°, and 2θ angle range 10° to 80°. The X-ray diffraction spectrum obtained by the test can be used to calculate the basal width La and longitudinal length Lc of the crystallite size according to the Scherrer equation, and the carbon interlayer spacing d002 according to the Bragg equation.

[0132] The "specific surface area" measurement method is measured according to the national standard "GB / T19587-2004 Gas Adsorption BET Method" using a dynamic nitrogen adsorption-desorption instrument.

[0133] The “ID / I G "Measurement method: Raman spectra of different materials were characterized by JY-H 800. The laser wavelength used was 632.8nm. The Raman spectra of all materials were at 1590cm -1 and 1355cm -1 There are two peaks on the left and right. For amorphous carbon materials, 1590cm -1 The peak at 1355cm is generally corresponding to the graphite crystal vibration mode in carbon materials, which is called the G peak, while the peak at 1355cm -1 The peak at the edge of the graphite corresponds to the defect vibration mode called D peak. D / I G is the area ratio of the two peaks.

[0134] The "first efficiency, 0.1C specific capacity, 4C specific capacity, and capacity retention rate after 1000 cycles" are all measured by electrochemical measurement methods. The specific test method is: assemble the battery, use the hard carbon negative electrode material of any embodiment and comparative example as the negative electrode active material, use polyvinylidene fluoride (PVDF) as a binder, and mix it evenly with conductive carbon black in a mass ratio of 90:5:5 in NMP (N-methylpyrrolidone) solvent, coat it into an electrode film, place it in a vacuum drying oven at 120°C and dry it for 12 hours, and obtain a hard carbon negative electrode sheet by rolling and punching; use a metal sodium sheet as a counter electrode, 1 mol / L NaPF6 (EC:DEC=1:1) as an electrolyte, and assemble the above-obtained hard carbon negative electrode sheets into 2032 button batteries in a glove box. Constant current charge and discharge test: at a current density of 0.1C, the voltage range is set to 0-2.5V, and the button half-cell is charged and discharged at a constant current. The first cycle discharge specific capacity and the first cycle charge specific capacity can be analyzed through the constant current charge and discharge curves. The first cycle charge specific capacity is the reversible specific capacity at 0.1C, and the ratio of the first cycle reversible specific capacity to the first cycle discharge specific capacity is the first coulomb efficiency. Rate test: the button half-cell is charged and discharged at different current densities. The charge specific capacity, i.e. the reversible specific capacity at 4C, can be analyzed from the charge and discharge curve at a current density of 4C. Cyclic performance test: repeated constant current charge and discharge are performed at a current density of 2C, and the reversible specific capacity after 1000 cycles is recorded. The ratio of this specific capacity to the first cycle reversible specific capacity is the capacity retention rate after 1000 cycles.

[0135] Table 1 Summary of physical and chemical properties and electrochemical performance of examples and comparative examples

[0136]

[0137]

[0138] It can be seen from the data in Table 1 that the hard carbon negative electrode materials prepared in various embodiments of the present invention have high specific capacity, good rate performance and excellent electrochemical properties when used in sodium ion batteries.

[0139] During the carbonization process of the hard carbon negative electrode material provided in Comparative Example 1, no metal chloride catalyst was added, and the prepared hard carbon negative electrode material had an underdeveloped pore structure and few sodium storage sites, resulting in a lower specific capacity when used in sodium ion batteries. In addition, the use of traditional high-temperature heat treatment resulted in large crystallite size and an interlayer spacing of less than 0.37 nm, which severely hindered the diffusion of sodium ions between layers. Therefore, the solid-phase diffusion rate was slow, exhibiting poor rate performance.

[0140] The hard carbon negative electrode material provided in Comparative Example 2 has not undergone microwave heat treatment, resulting in the microcrystalline layer structure not undergoing a rearrangement process, causing the layer structure to be disordered and the interlayer spacing to be greater than 0.39 nm, which cannot provide a fast ion transmission channel. Therefore, the material exhibits poor rate performance.

[0141] The hard carbon negative electrode material provided in Comparative Example 3 has not been coated by chemical vapor deposition, so that the surface area of ​​the material is high, and a large number of decomposition side reactions occur when the electrolyte contacts the carbon surface. Therefore, the first coulombic efficiency of the above material is low and the cycle performance is poor.

[0142] The above is only a preferred embodiment of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A high-performance hard carbon negative electrode material for sodium ion batteries, characterized in that: The macroscopic morphology of the hard carbon negative electrode material is powdery, and the microscopic morphology is irregular block particles, the particle size D50 of the irregular block particles is 5-10μm; the hard carbon negative electrode material has a microporous structure and a short-range close-packed layer structure inside, the pore diameter of the microporous structure is less than 2nm, the carbon layer spacing d002 of the layer structure is 0.37-0.39nm, the base plane width La of the crystallite size is 2-3nm, the longitudinal length Lc is greater than 1.5nm, and the Raman D peak intensity to G peak intensity ratio ID / IG is 2-3; the specific surface area of ​​the hard carbon material measured by nitrogen adsorption and desorption is less than 5m2 / g.

2. A method for preparing a high-performance hard carbon negative electrode material for sodium ion batteries, characterized in that: The following steps are involved: S1: mechanically mixing the carbon source precursor and the metal chloride solid to obtain a mixture A; S2: Under an inert atmosphere and at 400-600°C, the mixed material A is subjected to catalytic carbonization treatment to obtain solid B; S3: acid-washing and water-washing the solid B, and then drying to obtain a solid C; S4: in an inert atmosphere, subjecting solid C to microwave-assisted heat treatment at a temperature of 1100-1500° C. to obtain solid D; S5: crushing the solid D to obtain powder E; S6: Under the condition of 600-900° C., an organic gas is introduced to perform chemical vapor deposition treatment on the powder E to obtain the high-performance sodium ion battery hard carbon negative electrode material according to claim 1.

3. The method for preparing a high-performance hard carbon negative electrode material for sodium ion batteries according to claim 2, characterized in that: The carbon source precursor is selected from at least one of wood chips, fruit shells, bamboo chips, coconut shells, walnut shells, lignin and cellulose.

4. The method for preparing a high-performance hard carbon negative electrode material for sodium ion batteries according to claim 2, characterized in that: The metal chloride salt is selected from at least one of zinc chloride, cupric chloride, ferrous chloride and magnesium chloride, and the carbon source precursor and the metal chloride salt are mixed in a mass ratio of 1:1-1:

3.

5. The method for preparing a high-performance hard carbon negative electrode material for sodium ion batteries according to claim 2, characterized in that: In S2, the heating rate of the catalytic carbonization treatment is 5-10°C / min, and the time of the catalytic carbonization treatment is 60-240min.

6. The method for preparing a high-performance hard carbon negative electrode material for sodium ion batteries according to claim 2, characterized in that: In S3, the solid B is acid-washed and water-washed until the filtrate is neutral.

7. The method for preparing a high-performance hard carbon negative electrode material for sodium ion batteries according to claim 2, characterized in that: In S4, the heating rate of the microwave-assisted heat treatment is 50-100° C. / min, and the time of the microwave-assisted heat treatment is 10-40 min.

8. The method for preparing a high-performance hard carbon negative electrode material for sodium ion batteries according to claim 7, characterized in that: In S4, the microwave frequency of the microwave-assisted heat treatment is 2.4-2.6 GHz, and the microwave power is 0.5-1.4 kW.

9. The method for preparing a high-performance hard carbon negative electrode material for sodium ion batteries according to claim 2, characterized in that: In the step S6, the organic gas is selected from at least one of benzene, toluene, xylene, propane, butane, acetylene and methane, the flow rate of the organic gas is 1-100 L / min, and the reaction time of the chemical vapor deposition is 60-180 min.

10. The method for preparing a high-performance hard carbon negative electrode material for sodium ion batteries according to claim 2, characterized in that: The inert atmosphere is selected from at least one of nitrogen, argon and helium atmospheres.

Citation Information

Cited By

  • Preparation method of composite high-entropy hard carbon negative electrode material and sodium ion battery

    CN120864481A

  • Preparation method of composite high-entropy hard carbon negative electrode material and sodium ion battery

    CN120864481B